MKWK Curriculum as the Implementation of Knowledge Management in Higher Education - Zetty Karyati; Natalia Tri Astuti; Martinus Tukiran (Faculty of Science and Technology University of Pramita Indonesia, 2023)
The curriculum plays a very important role in the world of education, namely as a guide to educational goals so that it runs better. In order to increase competence and university graduates, the government launched the MKWK curriculum. This study aims to find out how the implementation of the MKWK curriculum as an implementation of knowledge management in improving the quality of university graduates (a case study was conducted at the Informatics Engineering Study Program, Faculty of Engineering and Computer Science, Indraprasta University PGRI, Jakarta). The method used in this study is descriptive analytic through a qualitative approach. Data collection techniques were carried out through literature studies and field studies using interviews, observation, and documentation studies. Data analysis was carried out through data reduction, data presentation, drawing conclusions and verification. The results found in this study are that in practice there are still many obstacles that hinder the smooth implementation of this curriculum. .